ANALISIS PEMBERLAKUAN TARIF MIKRO ANGKUTAN ANTAR KOTA TRAYEK KOTA GORONTALO PAGUAT - Haq, Idwar (Universitas Bina Taruna Gorontalo, 2024)
Analysis of the Implementation of Micro Tariffs for Inter-City Transport on the Gorontalo Paguat City Route. The aim of this research was to overcome the existence of micro drivers who charge their own transportation rates which are not in accordance with the provisions of established regulations. With the data collection method, interviews or in the context of this research, they are called informants. In this data source, the informants include the drivers, the Head of the Talaga Terminal Coordinator, Gorotalo City and the community, place, namely the data source obtained from a description of the situation and conditions related to the problem being discussed, Paper, namely the data source that presents signs in the form of letters. , numbers, images, or symbols. Based on the district regulation. Gorontalo number 28 of 2013 concerning adjustments to passenger transportation rates between cities, sub-districts and rural areas for economy class, namely Rp. 437.46,- /km/pnp. Based on these regulations, the Gorontalo-Paguat route is approximately 145km, namely Rp. 63,431,- or around Rp. 63,500,-. Meanwhile, the fare applied by micro drivers is Rp. 75,000. This is due to the large deposits made to the PO which covers the drivers, as well as the increasingly high cost of living necessities, therefore the government needs to review the determination of micro tariffs for public transport on the Gorontalo-Paguat route.